2020
DOI: 10.1021/acs.jpcc.0c05298
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Conductivity Stability of Metastable Tetragonal Phases in 1Yb2O3xSc2O3–(99 – x)ZrO2 (x = 7, 8 mol %)

Abstract: The present work studies the influence of 1 mol % Yb 2 O 3 codoping on the long-term conductivity stability in the metastable tetragonal phases present in 8−9 mol % Sc 2 O 3 −ZrO 2 . Dense polycrystalline samples are synthesized via conventional solid-state reaction and pressureless sintering methods. The 8 mol % dopant containing ZrO 2 compositions contain the metastable t′phase, while the t″-phase exists in the 9 mol % doped compositions. However, the grain conductivity values in all of the compositions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…The maximum conductivity degradation (10–16%) after 2000 h of aging was observed for compositions with a total concentration of stabilizing oxides equal to 8 mol%. Compositions containing 9 mol% of stabilizing oxides were relatively stable (conductivity degradation was 3%) [ 30 ]. Aging of (ZrO 2 ) 0.90 (Sc 2 O 3 ) 0.09 (Yb 2 O 3 ) 0.01 samples at 900 °C for 500 h led to a decrease in conductivity by 20% [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The maximum conductivity degradation (10–16%) after 2000 h of aging was observed for compositions with a total concentration of stabilizing oxides equal to 8 mol%. Compositions containing 9 mol% of stabilizing oxides were relatively stable (conductivity degradation was 3%) [ 30 ]. Aging of (ZrO 2 ) 0.90 (Sc 2 O 3 ) 0.09 (Yb 2 O 3 ) 0.01 samples at 900 °C for 500 h led to a decrease in conductivity by 20% [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is interest in studying the structure and transport characteristics of ceramic and crystalline samples of ZrO 2 -Sc 2 O 3 solid solutions additionally doped with Yb 2 O 3 [24][25][26]. The effect of long-term annealing at 650 • C in air on the properties of ZrO 2 solid solutions containing 8-9 mol% Sc 2 O 3 and additionally co-doped with 1 mol% Yb 2 O 3 has been studied [27]. It was shown that the introduction of 1 mol% Yb 2 O 3 reduces the degradation of the conductivity of ZrO 2 -Sc 2 O 3 solid solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In this order, Y 3+ (104 pm) Yb 3+ (100.8 pm), and Ce 4+ (101 pm) were mostly used as binary co-dopants. [19][20][21][22] Among these, 1 mol% ceria co-doped in 10 mol% scandia stabilized zirconia (1Ce10SSZ) became the popular choice of market leaders due to its remarkable conductivity (∼0.15 S cm −1 at 850 °C) along with minimum aging rate (∼15% in 4000 h at 850 °C) in air. 23 Furthermore, Omar et al 24 observe this aging behavior of 1Ce10SSZ in the air as well as reducing atmosphere at 600 °C.…”
mentioning
confidence: 99%
“…26 Apart from Ce 4+ , other co-dopants such as Y 3+ and Yb 3+ were also added in SSZ to suppress its aging behavior. 19,24,27 Politova and Irvine 27 examine the effect of systematic substitution of Sc 2 O 3 with Y 2 O 3 in 11SSZ. They found out that the presence of yttria in 11SSZ stabilized the cubic structure but reduced the conductivity as well.…”
mentioning
confidence: 99%